ICT clusters in development: Theory and evidence - Danny Quah (EIB Papers, 2001)
Many observers suspect economic growth to be inextricably associated with inequality: growth alone need not bring about unalloyed, uncontroversial increases in economic well-being because rising average income levels might come together with increasing disparities between rich and poor. Prominent theories on the sources of economic growth reinforce these concerns. Theories that especially do so are those that relate growth to increasing returns - where the more production occurs, the greater is productive efficiency - and to technological progress - where advances in science and knowledge are what drive economic growth (e.g., Aghion and Howitt, 1998; Grossman and Helpman, 1991; Romer, 1986, 1990). Versions of these theories imply a path dependence, where success breeds further success - those already rich or technologically advanced become more so; while those poor, similarly, become progressively poorer (Durlauf, 1993). Put another way, economic growth inevitably brings greater inequality.
Keywords: 330; Informationstechnik; Clusteranalyse; Regionales Wachstum; Theorie; EU-Staaten